Feudalism Judged by the Court of History: Medieval ‘Peasant Civilization - Gurevich, Aron Yakovlevich (Dějiny – teorie – kritika, 2008)
This Czech translation of an essay, originally written in Russian and published in 2004, considers the Western historians’ conception of feudalism of the last three decades. Drawing from research into Scandinavian archive documents, the author points to the limits of the approaches taken so far. They have, he argues, been determined both by the extant records and by the transfer of Latin terminology to a vernacular milieu in which Latin terms can indicate social categories and property relations different from what they originally meant. He also comments critically on the highly developed twentieth-century Russian research into feudalism, in which works based on thorough analysis of west European records are predominant. He also considers in detail the existing approach to family/clan ownership and, again referring to Scandinavian sources, demonstrates that the usual claims must be fundamentally reassessed.